Removal of Chromate from Aqueous System by Activated Red-Mud - Dursun, Sukru; Guclu, Dunyamin; Berktay, Ali; Guner, Tunc (Asian Journal of Chemistry, 2010)
In this investigation, red-mud which is the semi-waste of the Seydisehir Aluminium Factory in Turkey was used as an adsorbent material after activation processes. Firstly, the redmud was treated with different concentration of HCl acid and was washed up with deionized water to clean the acid and other residues. Then, activate adsorbent was used in different doses and at the different pH values for each experimental test. Furthermore, optimum activated red-mud dosage was added in the water containing different chromate concentration. So, the capability of the red-mud for the chromate removal from the water was investigated. In the experiments, the chromate added tap water was used for synthetic water samples. About 70 % chromate removal efficiency was obtained by the optimum red-mud dose and pH value. This investigation indicated that waste of aluminium factories might be used for heavy metal removal processes from the water.